Menghidupkan Warisan Sejarah Melalui Aksi Bersih dan Pelestarian Lingkungan di Kawasan Candi Muara Takus XIII Koto, Kab. Kampar, Riau - Andres M. Ginting; Asnewastri Asnewastri; Ahmad Fakhri Hutauruk; Jalatua H. Hasugian; Satria Chandra; Jonatan Sijabat; Yohannes Setiawan Zega; Dora Ani Putri Damanik (Lembaga Pengembangan Kinerja Dosen, 2026)
Muara Takus Temple is a valuable historical heritage in Riau Province and a testament to the glory of ancient civilization in the Indonesian archipelago. However, the environment around the temple often faces problems such as litter, vegetation damage, and declining public awareness. Clean-up and environmental preservation activities in this area demonstrate the involvement of the younger generation and the community in preserving the historic site. Through a participatory approach, this community service program aims to describe the process, results, and social impact of preservation activities in the Muara Takus Temple area. The results of the community service program demonstrate increased public awareness, the formation of cross-institutional collaboration, and the strengthening of the value of mutual cooperation in preserving cultural heritage and the environment. The results demonstrate that the involvement of the community, students, and site managers has successfully raised collective awareness of the importance of maintaining cleanliness and preserving cultural heritage. Furthermore, this activity strengthened the synergy between historical and environmental preservation through tree planting, waste management, and the provision of educational boards. This activity demonstrates that cultural heritage preservation can be revitalized through active participation and cross-generational collaboration.